Helicobacter pylori arginase inhibits nitric oxide production by eukaryotic cells: A strategy for bacterial survival - Gobert, Alain P. (The National Academy of Sciences, 2001)
The antimicrobial effect of nitric oxide (NO) is an essential part of innate immunity. The vigorous host response to the human gastric pathogen Helicobacter pylori fails to eradicate the organism, despite up-regulation of inducible NO synthase (iNOS) in the gastric mucosa. Here we report that wild-type strains of H. pylori inhibit NO production by activated macrophages at physiologic concentrations of l-arginine, the common substrate for iNOS and arginase. Inactivation of the gene rocF, encoding constitutively expressed arginase in H. pylori, restored high-output NO production by macrophages. By using HPLC analysis, we show that l-arginine is effectively consumed in the culture medium by wild-type but not arginase-deficient H. pylori. The substantially higher levels of NO generated by macrophages cocultured with rocF-deficient H. pylori resulted in efficient killing of the bacteria, whereas wild-type H. pylori exhibited no loss of survival under these conditions. Killing of the arginase-deficient H. pylori was NO-dependent, because peritoneal macrophages from iNOS(−/−) mice failed to affect the survival of the rocF mutant. Thus, bacterial arginase allows H. pylori to evade the immune response by down-regulating eukaryotic NO production.